The Impact of Changes in Exhaust Temperature on the Power Output and Heat Rate of a Gas Turbine with a Capacity of 238 MW - Parapa', Hendra Budiono Putra (INTEK: Jurnal Penelitian, 2021)
The exhaust temperature parameter is one of the parameters that need to be considered in maintaining the performance of the gas turbine. The purpose of this study is to analyze the effect of changes in exhaust temperature on power output and heat rate. The data used is the actual design data of the M701 gas turbine. This data is used in building the model using the GateCycle software. The modeling simulation results are then validated using the actual design data. To see the impact of changes in exhaust temperature, data from the latest gas turbine performance results are used. This study concludes that changes in exhaust temperature parameters of 1OC have an impact on changes in power output of 0.273% and heat rate of 0.047%.